Answer:
Exactly one
Step-by-step explanation:
Solve your equation step-by-step.
2(x−3)−17=13−3(x+2)
Simplify both sides of the equation.
2(x−3)−17=13−3(x+2)
Simplify
2x−23=−3x+7
Add 3x to both sides.
2x−23+3x=−3x+7+3x
5x−23=7
Add 23 to both sides.
5x−23+23=7+23
5x=30
Divide both sides by 5.
5x/5 = 30/5
x=6
Step-by-step explanation:
here's the solution,
in the given figure , sum of all angles formed with O measures 360°
because, it forms a complete angle
so,
=》mPOQ + mQOR + mROS + mSOT + mTOP = 360°
=》mPOQ + mQOR + mROS + mSOT + mTOP = (90° × 4)
=》mPOQ + mQOR + mROS + mSOT + mTOP = 4 × right angle
(cuz.. right angle = 90°)
Try to make sense out of this problem to where you can understand it
Answer:
110 pages
Step-by-step explanation:
Day 1 =x
Day 2 =2x
Day 3 =x-6
(x)+(2x)+(x-6)=458
Add likes together.
4x-6=458
4x=464. Divide both sides by 4 to get x. X=116
Day 3=116-6=110